Liquid–liquid phase separation of Tau by self and complex coacervation. (19th May 2021) - Najafi, Saeed; Lin, Yanxian; Longhini, Andrew P.; Zhang, Xuemei; Delaney, Kris T.; Kosik, Kenneth S.; Fredrickson, Glenn H.; Shea, Joan‐Emma; Han, Songi
Abstract: The liquid–liquid phase separation (LLPS) of Tau has been postulated to play a role in modulating the aggregation property of Tau, a process known to be critically associated with the pathology of a broad range of neurodegenerative diseases including Alzheimer's Diseas e. Tau can undergo LLPS by homotypic interaction through self‐coacervation (SC) or by heterotypic association through complex‐coacervation (CC) between Tau and binding partners such as RNA. What is unclear is in what way the formation mechanisms for self and complex coacervation of Tau are similar or different, and the addition of a binding partner to Tau alters the properties of LLPS and Tau. A combination of in vitro experimental and computational study reveals that the primary driving force for both Tau CC and SC is electrostatic interactions between Tau‐RNA or Tau‐Tau macromolecules. The liquid condensates formed by the complex coacervation of Tau and RNA have distinctly higher micro‐viscosity and greater thermal stability than that formed by the SC of Tau. Our study shows that subtle changes in solution conditions, including molecular crowding and the presence of binding partners, can lead to the formation of different types of Tau condensates with distinct micro‐viscosity that can coexist as persistent and immiscible entities in solution. We speculate that the formation, rheological properties and stability of Tau droplets can be readily tuned by cellular factors, and that liquid condensation of Tau can alter the conformational equilibrium of Tau.